PENGGUNAAN KAPANG (Trichoderma viride) DALAM PEMBUATAN SIRUP GLUKOSA RUMPUT LAUT (Eucheuma spinosum) - ANDRI KURNIAWAN (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2009)
Glucose syrup is an aqueous solution liquid that produced from strach hidrolysis with use enzyme catalisator, acid, or combination between enzyme and acid. Glucose syrup is secondary product which more used in food and drink industries, substrate for fermentation, or even used as raw material for chemical materials productions like ethanol and acetat acid. Glucose can be produced with used cellulose with breaking down cellulose is as polysaccharide to its monomer, that glucose. One of cellulose source that very much in the nature is seaweed. Cell wall of seaweed specially from red algae and green algae is cellulose. How ever, cell wall of brown algae is mixed of cellulose and algin acid (Tortora et al, 2001). Fiber compotitions of E. spinosum 5,936% and E. cottonii 5,478% (Ayu, 2007). The used data analysis are substrate concentration has 3 levels that 1% (K1), 3% (K2), dan 5% (K3) and fermentation time has 4 levels, that 2 days (H1), 4 days (H2), 6 days (H3), and 8 days (H4) and each repeated 3 times. In the process of seaweed E. spinosum fermentation by Fungi T .viride has been carried out in K2H3, that in substrate concentration 3% and fermentation time 6 days include glucose value 6,242%, pH value 8,9, total solved solution 2,3% brix, color L 43,32, and hidrolized cellulose percentage 3,90%